The effect of nanosilver and chlorhexidine mouthwash on anaerobic periodontal pathogens counts - Al-Sharani, Amani Abdulhakeem; Al-Hajj, Waddah; Al-Shamahy, Hassan A.; Jaadan, Bushra Mohammed (Society of Pharmaceutical and Medical Professionals (SPMP), 2019)
Objective: The necessitate for frequent application of Chlorhexidine (CHX), and other side effects has encouraged the search for option that are more suitable for patients as nanosilver mouthwash (NS). So the aim of this study was to determine the effects of a mouthwash made with nanosilver on dental plaque microbial counts and compare it with commercially available Chlorhexidine. Methods: Sixty two plaque induced gingivitis patients were allocated into two groups and asked to rinse with 10 ml of NS and CHX, immediately after brushing, for 1 min, in the morning and evening. Sub gingival plaque microbial counts were taken at baseline, two weeks, and finally at four weeks for each patient. Subsequently, the samples were collected, transferred and cultured in blood agar in anaerobic media. The colonies were counted and expressed as CFUs. The statistical analysis between CFUs variables within groups was calculated and the variation significance was calculated by performed t-test. Results: It is very obvious that the values of CFU decreased significantly (p<0.001) as the time of use nanosilver until reaching the highest value when the time of use was 4 weeks [70.347 to 32.424.6 (2 weeks), and 14.29.9 (4 weeks) with inhibition of growth rate after 2 weeks was 46% and after 4 weeks was 79.7%. The effect of commercially available CHX mouthwash was approximately similar to the effect of NS mouthwash used. Conclusion: In conclusion, both Group I and Group II showed similar effect on inhibition anaerobic periodontal pathogens counts and gingival health. There was significant inhibitory effect on microbial counts where NS mouth-wash had shown better results than CHX, but there was no significant difference between the nanosilver mouth wash and the Chlorhexidine mouthwash.